ПРАВОВЕ РЕГУЛЮВАННЯ ДІЯЛЬНОСТІ ГРОМАДСЬКИХ ОБ’ЄДНАНЬ У РОСІЙСЬКІЙ ІМПЕРІЇ У ХІХ - НА ПОЧАТКУ ХХ СТ. - ДОЦЕНКО, Віктор Олегович, ЛОЩИХІН Олександр Миколайович (SUPREMANCE OF LAW, 2016)
In the article are analyzed the features of formation of Russian imperial legislation which was aimed to regulate the activities of NGOs during the nineteenth century. Formation of Russian legislation which regulates the activities of public associations began in the eighteenth century. In the early nineteenth century Russian imperial institutions regulated the activities of public institutions through the publication of standard statutes for voluntary sector partnerships. The policy of the Russian imperial government’s voluntary societies actively started taking shape in the second half of the nineteenth century and it was accompanied by the formation of a legal framework for the regulation of their activities. Since 1890 Russian Empire began the process of re-registration of voluntary associations. Government and ministries began to issue charters to model associations certain areas in early XX century. Russian Empire formed a system of administrative and legal regulation of NGOs. But it required improvement. First, it was necessary to create a clear system of control over the activities of NGOs, associations and unions. Secondly, it was necessary to strengthen the ties between public organizations and state authorities in central and local government to implement the declared social, political and economic transformation.